Dimensionamiento de estructuras de acero - Del Valle Calderón, Enrique; Colinas Villoslada, Félix; Martínez Romero, Enrique (My University, 1975)
The process of designing a structure is often thougth of as arranging elements or forms in such a way that the expected loads are carried safely. Whereas the ability to support load is perhaps the most important requirement in design, there are three over-all objectives to be met if a structural design is to be satisfactory.
Keywords: reglamentos de edificios; diseño plástico; factor de seguridad; aceros al carbón; rolado en frío